Retaining Landau quasiparticles in the presence of realistic charge fluctuations in cuprates - Yamase, Hiroyuki (2024)
Charge excitation spectra are getting clear in cuprate superconductors in momentum-energy space especially around a small momentum region, where plasmon excitations become dominant. Here, we study whether Landau quasiparticles survive in the presence of charge fluctuations observed in experiments. We employ the layered t-J model with the long-range Coulomb interaction, which can reproduce the realistic charge fluctuations. We find that Landau quasiparticles are retained in a realistic temperature and doping region, although the quasiparticle spectral weight is strongly reduced to 0.08-0.24. Counterintuitively, the presence of this small quasiparticle weight does not work favorably to generate a pseudogap.